Sunflowers, magnolia trees & other flowering plants - Parker, Steve
This book introduces you to a well known group of plants, from bright sunflowers to beautiful magnolia trees. It explores the history of flowering plants and examines the way flowering plants reproduce and obtain energy. It also looks at the various uses for flowering plants, including decoration and agriculture.
Keywords: Angiosperms; Flowers; Plants